58th Open Seminar on Acoustics joined with 2nd Polish-German Structured Conference on Acoustics - Roman Salamon; Eugeniusz Kozaczka; Grażyna Grelowska (Archives of Acoustics)
The 58th Open Seminar on Acoustics and 2nd Polish-German Structured Conference on Acoustics are organized by the Gdańsk Division of the Polish Acoustical Society, the latter jointly with the German Acoustical Society DEGA. These scientific events are going to be held in the Delfin Hotel in Jurata on Hel Peninsula on 13 – 16 September 2011. The topics of the papers submitted to the 58th Open Seminar on Acoustics cover a large area of theoretical, technical and experimental research in the field of acoustics. The 2nd Polish-German Structured Conference on Acoustics will be held in the following sections: multi-modal and object-oriented approaches to audition, computational acoustics, active noise control, room and building acoustics, and seabed acoustics. Five invited papers will be delivered by the following speakers: 1. Prof. Otto von Estorff Hamburg University of Technology, Hamburg; 2. Prof. Grażyna Grelowska Polish Naval University, Gdynia; 3. Prof. Marek Iwaniec AGH University of Science and Technology, Kraków; 4. Prof. Andrzej Nowicki Institute of Fundamental Technological Research Polish Academy of Sciences, Warszawa; 5. Prof. Anna Preis Adam Mickiewicz University, Poznań. The 58th Open Seminar on Acoustics and 2nd Polish-German Structured Conference on Acoustics together have received 115 papers. Some abstracts of these papers are given below.